RUDYARD KIPLING’S LIFE AND HIS POETRY - Majitova Feruza Gayrat qizi; Xamitov Eldorbek Erkin o`g`li (Ta’lim innovatsiyasi va integratsiyasi, 2024)
This article explaines the life and events of Rudyard Kipling’s life. Along with this, the article also talks about Rudyard’s works and their analysis.